Assessment of Solvent Extraction using Sonication to Recover Tryptophan from Kappaphycus alvarezii (Doty) Doty ex Silva: Experimental and Modelling - Putra, Venansius Galih Perkasa; Chaniago, Weni; Izmi, Nuzulia; Mutiarahma, Selma; Kurnia, Kiki Adi; Palma, Miguel; Setyaningsih, Widiastuti (Trends in Sciences, 2024)
The application of Kappaphycus alvarezii in the food system has attracted researchers due to its bioactive compounds, including tryptophan. The present study was conducted to extract tryptophan from K. alvarezii with the aid of sonication. A reduced multilevel factorial design was conducted to evaluate the effect of solvent, ultrasound power, duty-pulse cycle, time and temperature on the recovery of tryptophan. Analysis of variance suggested that the type of solvent and combination setting of power and duty-pulse cycle significantly influenced the extraction (p < 0.05). In contrast, extraction time and temperature did not alter the extraction (p > 0.05). The optimum was using ethanol, ultrasound power 80 %, pulse duty-cycle 0.8 s–1, extraction time 10 min, and temperature 25 °C and tryptophan concentration was 56.41 ± 2.42 mg L–1. Subsequently, a COnducto-like Screening MOdel for Real Solvent (COSMO-RS) was performed to clarify the impact of solvent affinity and polarity on the tryptophan extraction from K. alvarezii. HIGHLIGHTS Ultrasound-assisted extraction and HPLC-DAD were used to determine tryptophan levels in alvarezii. Box-Behnken design, in conjunction with the response surface methodology, effectively optimized the extraction conditions. COSMO-RS successfully predicted the solubility of tryptophan extracted from alvarezii using different solvents. GRAPHICAL ABSTRACT